Gold pawn services and sustainable financial inclusion: The roles of service convenience, perceived value, customer engagement, and institutional trust - Sabda Aji Kurniawan; Martha Racwel Patty; Sulastri Handayani (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: Financial inclusion has increasingly shifted from a primary focus on access expansion toward the challenge of sustaining long-term usage of formal financial services. Although gold-based financial services are widely positioned as accessible entry points for unbanked and underbanked populations, their contribution to sustainable financial inclusion from a behavioral perspective remains insufficiently understood. This study aims to examine how perceived value, service convenience, and customer engagement influence continuance intention to use financial services through the mediating role of institutional trust, while also assessing the moderating effect of financial literacy within a post-adoption and trust-based continuance framework. Methods: A quantitative explanatory design was employed using survey data collected from 332 users of gold pawn services selected through stratified random sampling across Western, Central, and Eastern Indonesia, and analyzed using Partial Least Squares Structural Equation Modeling. Findings: The results indicate that perceived value and customer engagement significantly enhance institutional trust but do not directly influence continuance intention, whereas service convenience exerts both direct and indirect effects on sustained usage. Institutional trust emerges as a central mechanism that transforms evaluative and relational factors into long-term behavioral commitment, while financial literacy does not significantly moderate the trust–continuance relationship, suggesting that institutional credibility outweighs individual financial capability. Conclusion: Overall, the findings suggest that in high-risk financial service contexts, continuance behavior is governed primarily by institutional trust rather than by value assessments or individual financial literacy, thereby establishing operational simplicity and service reliability as the core foundations of sustainable financial inclusion. Novelty/Originality of this article: This study contributes novel insights by revealing the asymmetric roles of value, convenience, and engagement in shaping continuance behavior and by identifying a trust substitution effect in which institutional trust supersedes financial literacy in driving sustained participation in formal financial services.